PENGENALAN KIRAB KEBUDAYAAN GREBEG SURO DI DESA KALIPANG MELALUI MEDIA SOSIAL - Fauziyah Laili, Ummiy; Wahyu Wulandari, Ratna; Riska Destiana, Lusi; Hidayati, Nur; Amilatul Afifah, Rizki (Proceedings of Annual Conference on Community Engagement, 2023)
In the era of globalization, the rapid development of science and technology, one important aspect is the presence of social media, has allowed the spread of various cultures. One of these cultural traditions is the Grebeg Suro procession held in Kalipang Village, Grogol District, Kediri Regency, East Java. This community service activity aims to introduce Grebeg Suro culture in Kalipang Village through social media, namely TikTok and Instagram, so that this tradition is better known to a wide audience. The implementation and documentation of this community service uses a virtual ethnographic approach, which involves qualitative data analysis, with conclusions drawn from direct observations, interviews, and field observations. Positive responses from users and the community have emerged, in line with the recognition of the benefits derived from videos. The informative content of the video is enough to illustrate the cultural diversity that develops in Kalipang Village. In addition, the results of the post-viewing survey show the desire of the community to visit Kalipang Village. Overall, the introduction of the Kalipang Villaget Cultural Kirab tradition through social media videos is clear evidence of how digital strategies can revive local cultural heritage and expand its reach to a wider level. The results achieved through this approach provide opportunities for deeper cultural collaboration.